Influence of metakaolin as partially cement replacement minerals on the properties of cement and concrete / Muhd Norhasri Mohd Sidek ...[et al.] - Mohd Sidek, Muhd Norhasri; Arshad, Mohd Fadzil; Megat Johari, Megat Azmi; Mohd Yazid, Zaid; R, Amir Khomeiny (Research Management Institute, 2012)
Metakaolin is a manufactured pozzolan produced by thermal processing of purified kaolinitic clay using electrical furnace. This study has examined the effect of Metakaolin on the properties of cement and concrete at a replacement level of 0%, 5%, 10% and 15%. The parameters studied were divided into two groups which are chemical compositions, water requirement, setting time and soundness test were carried out for cementitous properties. Workability, compressive strength and bending strength were test for concrete properties. Hardened concrete was cured under different type of curing conditions and tested.. The result showed that the inclusions of Metakaolin as cement replacement minerals have change some of the cementitous and concrete properties. This research reveals, the optimum effect for cementitous and concrete properties for metakaolin was 10%.